2015
DOI: 10.4238/2015.april.17.4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of ketamine on acute spinal cord injury in rats

Abstract: ABSTRACT. The aim of this study was to investigate the neuroprotective effects of ketamine during acute spinal cord injury in rats. Sprague Dawley (SD) rats (N = 70) were randomly divided into three groups: sham-operated (N = 10), control (N = 30), and treatment (N = 30) groups. The moderate spinal cord injury model was established. After injury, the sham-operated group received no drug, the treatment group received intraperitoneal ketamine injections, and the control group received intraperitoneal normal sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Currently, isoflurane has been suggested as a replacement for chloral hydrate, because it is easy to administer and to titrate, has a rapid onset and recovery period, an adequate and reproducible anesthesia depth, minimal cardiac depression, and ethical considerations (Maud et al, 2014). Although previous studies demonstrated that anesthetics including ketamine, isofl urane, and halothane had potential neuroprotective effects (Kapinya et al, 2002;Xiong et al, 2003;Kitano et al, 2007b;Wang et al, 2008;Deng et al, 2014;Tang et al, 2015), isoflurane can be an appropriate anesthetic agent when establishing the MCAO model (Kitano et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, isoflurane has been suggested as a replacement for chloral hydrate, because it is easy to administer and to titrate, has a rapid onset and recovery period, an adequate and reproducible anesthesia depth, minimal cardiac depression, and ethical considerations (Maud et al, 2014). Although previous studies demonstrated that anesthetics including ketamine, isofl urane, and halothane had potential neuroprotective effects (Kapinya et al, 2002;Xiong et al, 2003;Kitano et al, 2007b;Wang et al, 2008;Deng et al, 2014;Tang et al, 2015), isoflurane can be an appropriate anesthetic agent when establishing the MCAO model (Kitano et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Given the present data and those of previous studies, it may be concluded that inflammatory markers are expressed differently between various types of ketamine-treated cells ( 48 ). Numerous studies regarding antidepressants and neural pathways have indicated that ketamine is associated with the downregulation of proinflammatory cytokines, including IL-6 ( 36 , 49 ). In addition, the expression of IL-6 was positively correlated with the migration of vascular SMCs ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 66 patients with aneurysmal subarachnoid hemorrhage, (S)-ketamine infusion (with a mean dose of 2.8 ± 1.4 mg/kg/hour) significantly decreased the incidence of spreading depolarizations [142]. While the role of ketamine in spinal cord injury has been shown in animal models [143,144], this has not yet been translated to human research.…”
Section: Neurologic Applications Of Ketaminementioning
confidence: 99%